Upaya Membangkitkan Ekonomi Masyarakat Melalui Zakat Dalam Pajak Penghasilan - Della Fadhilatunisa (CV. Sakura Digital Nusantara, 2023)
Poverty is still an unresolved problem in Indonesia. The unequal distribution of wealth is the cause of the rise and fall of the poverty level. On the other hand, the problem facing Indonesia is the infrastructure sector. The low quality of infrastructure hampers the pace of the country's economy. These two problems make it difficult for the Indonesian economy to develop. So, the formulation of the problem raised in this study is how is the relationship between zakat and income tax and its relationship with efforts to generate the community's economy. The purpose of this research is to find out the solution to the existing problems through zakat and taxes. In Islam, zakat is used as a distribution of wealth from the giver (muzakki) to the recipient (mustahik). Meanwhile, in state regulations, one of the funds obtained from taxes is allocated to infrastructure development. Zakat and taxes play an important role in the country's economy, zakat solves problems on a micro level while taxes solve problems on a macro level.